Beyond memory loss: Addressing dementia awareness and care in Pakistan” - Syeda Ayesha Nadeem; Iman Siddiqui (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Dementia is a syndrome caused by various diseases that gradually destroy nerve cells and damage the brain, typically leading to cognitive decline beyond normal ageing.(1) Currently, 58% of people with dementia live in low- and middle-income countries, a figure expected to rise to 68% by 2050.(2) In view of the increasing cases in countries like Pakistan, we aim to highlight risk factors, prevention, management and social stigma surrounding dementia. The risk of dementia increases with age, especially after 65, but it is not a normal part of aging. A family history raises the likelihood of developing it, though it can also occur without one. Excessive alcohol consumption, elevated low-density lipoprotein levels, diabetes, and smoking are significant risk factors. Studies show that individuals over 50 with traumatic brain injuries (TBI) have a higher risk of dementia and Alzheimer's disease. However, research suggests that adopting a healthy lifestyle with proper diet and exercise can reduce the risk of cognitive decline.(3) There is no definitive cure for dementia, but interventions such as physical activity, occupational therapy, and a supportive care environments can improve patients' quality of life. Medications like cholinesterase inhibitors, NMDA receptor antagonists, lecanemab, and donanemab may slow disease progression and alleviate symptoms.(1) Despite its growing prevalence, dementia remains a low priority in Pakistan's healthcare system. Studies have shown that public awareness of dementia remains inadequate, with many perceiving it as a normal aspect of ageing or a sign of weakness. This stigma and misconception lead to delayed diagnoses and inadequate patient care. Socioeconomic disparities further hinder management, as middle- and low-income households often lack access to trained caregivers, relying instead on untrained relatives, which increases the risk of inadequate care. Employing specialized dementia caregivers can significantly enhance patient outcomes by providing personalized attention, managing behavioural challenges, and ensuring a safe, familiar environment.(4) Public awareness campaigns through television, print, and digital platforms should emphasize early symptom recognition, common misconceptions, proper care strategies and affordable healthcare options. Beyond awareness, nationwide policies, laws, and systems are crucial to ensure that individuals with dementia receive the care they deserve. Pakistan, known for its strong philanthropic culture, has a substantial number of high-net-worth individuals who could be encouraged to invest in dementia research and healthcare infrastructure. A long-term goal should be to position Pakistan as a key contributor to international clinical neuroscience research and education, providing valuable data to global brain health consortiums.(2)